Agrotóxicos, transgênicos na agricultura e saúde humana no estado do Paraná-Brasil - Seghese, Marcos Alberto (2016)
The State of Paraná stands out for being responsible for over 20% of the national production of grains. The Paraná agriculture makes heavy use of inputs commercially available, being the third largest national agrochemical consumer. In the current agricultural model, the application of pesticides is required to obtain good productivity levels, endangering human health and other species, negatively impacting the environment. Distributors and sellers of pesticides in general are much more concerned with the sales quotas than with safety. In this hegemonic model of agriculture dominates the economic dimension (profit and power), destroying the ecological dimensions, political, social, ethical, cultural and others. The food is turning into a commodity (an industrial product) increasingly focused and determined by a few transnational companies. Power is being dominated by the private logic of capital, creating a producer scenario of diseases and economic and social inequalities. The Brazilian state is losing the Food and Nutritional Security and Human Rights will adequate food, compromising the entire public health and guarantee of human rights, capitalism fruit by the Green Revolution tax field. The general farmers have low educational level and lack of information about the negative impacts of the Green Revolution in this way is an urgent public policies that make the face of all these problems described above, and promote a critical reflection on the paths to be followed in towards sustainable agriculture while preserving the environment for this generation and for future generations, as otherwise we anticipated the sixth mass extinction on Earth.